(untitled) (Research, Society and Development, 2022)
PIBID is a program destined at undergraduate students who are in the process of training, and it is considered a pillar for the improvement of teaching practice and for basic education as a whole. The main objective of this work is to show the importance that the program has for the formation of these future teachers. Based on the above, the work was developed in two stages, the first consisted of a bibliographic research, where we searched a database for what authors have already published about PIBID, and the other way was the application of a questionnaire applied to the scholarship holders of the program, being students of the Licentiate Course in Sciences: Mathematics and Physics, from ISB/Coari. This questionnaire was made available online through the Google Form resources. Therefore, this research showed the importance of the PIBID Program in the training of undergraduates who worked in this program from 2020 to 2022, at the CETI-COARI school. In the students’ view, this period of experience on the school floor improved their professional development and their ways of seeing and living the role of teacher. It is worth remembering that the degree courses have in their curriculum the supervised internship, which is mandatory. On the other hand, the current research shows that the benefits of PIBID go far beyond the benefits provided by the Supervised Internship, since it became evident, through the analysis of some theorists, that the Supervised Internship is not enough for the complementary training of future teachers.